2016
DOI: 10.18632/oncotarget.14393
|View full text |Cite
|
Sign up to set email alerts
|

Emetine elicits apoptosis of intractable B-cell lymphoma cells with MYC rearrangement through inhibition of glycolytic metabolism

Abstract: Despite improved clinical outcomes of diffuse large B-cell lymphoma, a certain proportion of patients still develop a primary refractory disease. To overcome these lymphomas that are intractable to existing treatment strategies, the tumor microenvironment has been identified as a potential therapeutic target. Here we describe our search for effective drugs for primary refractory lymphoma cells with MYC rearrangement. Through the drug screening of 3,440 known compounds, we identified a unique compound, emetine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…We have previously reported that the BLS4 mouse FRC line, which was established from a mouse lymph node, enabled culture of PDX lymphoma cells and that CAF also supported survival of primary patient lymphoma cells in vitro . Primary patient lymphoma cells (Pt#8 with Burkitt lymphoma, and Pt#9 with high‐grade B‐cell lymphoma, not otherwise specified) could proliferate in coculture with CAF#1 and CAF#2 in vitro, whereas neither cell type could survive in monoculture (Figure A,B; Table ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…We have previously reported that the BLS4 mouse FRC line, which was established from a mouse lymph node, enabled culture of PDX lymphoma cells and that CAF also supported survival of primary patient lymphoma cells in vitro . Primary patient lymphoma cells (Pt#8 with Burkitt lymphoma, and Pt#9 with high‐grade B‐cell lymphoma, not otherwise specified) could proliferate in coculture with CAF#1 and CAF#2 in vitro, whereas neither cell type could survive in monoculture (Figure A,B; Table ).…”
Section: Resultsmentioning
confidence: 96%
“…Generally, the TME is known to be under hypoxic conditions and promotes a metabolic switch in tumor cells away from mitochondrial respiration to glycolysis . According to our previous report, tumor cells in coculture with CAF promote anaerobic glycolysis as indicated by the increased expressions of HK2 and PDK1 . Considering the complexity in terms of energy production in tumor cells, tumor cells might coordinate the regulation of aerobic glycolysis and the citric acid cycle according to the specific TME .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAPK signaling is a complicated process involved in the pathogenesis of human disorders ranging from cancers and neurodegenerative diseases. The stimulation of MAPK cascades leads to disease development by initiating neuronal apoptosis (34). Inhibitors of ERK1/2, MEK, JNK, and p38 MAPK are considered to be potential drugs for many diseases including cancer (35).…”
Section: O21mentioning
confidence: 99%